EVALUASI PERENCANAAN FONDASI CERUCUK BAMBU PADA GEDUNG KAMPUS I UNIVERSITAS MUHAMMADIYAH SUMATERA BARAT - Febri Yanti, Endah; Dewi, Selpa; Ishak, Ishak (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The Rectorate Building of Muhammadiyah University of West Sumatra located in Pasir Jambak, Padang City. This building is situated in a coastal area. Prior to commencing construction, a feasibility study of the land must be conducted to determine the content and condition of the soil upon which the building will be erected. To address soil subsidence caused by clayey soil, substantial bearing capacity is required to avoid significant settlement. In this case, the bearing capacity is provided by shallow foundations reinforced with bamboo piles, thus ensuring substantial support. The method employed is evaluation, which involves analyzing foundation bearing capacity using foundation bearing capacity equations, and then assessing settlement with several options for the number of bamboo piles using the Plaxis application. Based on the analysis results, soil liquefaction occurs at ground elevations of 0-3 meters. The foundation bearing capacity without piles, as determined by the Terzaghi equation, is 478 kN with a settlement of 54mm. Meanwhile, with bamboo pile reinforcement, the foundation bearing capacity for option 1 and option 2 are 705.7 kN and 925.5 kN respectively. Settlement with option 1 and option 2 is 25.7mm and 18.5mm respectively. The installation of bamboo piles at the base of this shallow foundation provides a twofold increase in soil bearing capacity compared to the original, thereby reducing settlement experienced by the shallow foundation after reinforcement.Keywords: Settlement, Foundation, Soil, Bamboo Pile.